Analysis of the effects of cannabinoids on identified synaptic connections in the caudate-putamen by paired recordings in transgenic mice - Freiman, Ilka (Blackwell Science Inc, 2006)
CB(1) cannabinoid receptors are expressed in many neurons in the caudate-putamen. However, it is not known how the activation of these receptors influences synaptic transmission between different neuron classes. The aim was to establish a method for studying identified synaptic connections in the caudate-putamen, and to determine the effects of cannabinoids on these connections. Brain slices were prepared from transgenic mice expressing enhanced green fluorescent protein (EGFP) in parvalbumin-positive fast spiking interneurons (PV-FSNs). PV-FSNs were identified based on their fluorescence. Non-fluorescent medium-sized neurons were considered to be medium spiny neurons (MSNs). Synaptic transmission was studied by simultaneous patch-clamp recording from identified neuron pairs. In the case of PV-FSN → MSN neurotransmission, the synthetic cannabinoid receptor agonist WIN55212-2 lowered the success rate of transmission and the amplitude of successful postsynaptic events. Analysis of miniature inhibitory postsynaptic currents indicated that WIN55212-2 inhibited synaptic transmission presynaptically. WIN55212-2 did not elicit somatodendritic effects in PV-FSNs: membrane potential, membrane current and evoked firing were not changed. WIN55212-2 also depressed the MSN → MSN neurotransmission. The inhibitory synaptic input to MSNs was only weakly suppressed by endocannabinoids released by depolarized postsynaptic MSNs. The results show that the combined use of transgenic animals and paired-recording techniques allows the study of synaptic connections between rare neurons. Using these techniques, we showed that activation of CB(1) receptors on axon terminals of (i) PV-FSNs and (ii) MSNs leads to presynaptic inhibition of GABAergic synaptic transmission between these axons and their postsynaptic targets, the MSNs. The cannabinoids acted preferentially on axon terminals without effects on the somatodendritic region of the neurons.